Taonsayontenhroseri:ye'ne: the power of art in Indigenous research with youth. (June 2019) - Whitlow, Kawennakon Bonnie; Oliver, Vanessa; Anderson, Kim; Brozowski, Kari; Tschirhart, Stephanie; Charles, Danielle; Ransom, Kaienkwinehtha
Through artistic, spiritual, and ceremonial practices, and cultural bridging between Indigenous communities, our project sought to create a social environment that fostered an exchange of cultural traditions, created opportunities for internationalized decolonization, and fostered pride in Indigenous identities. This arts-based research project used and invoked symbols and images from Haudenosaunee culture, making them relevant to young people through graffiti art created by and for young Indigenous people. This article reflects on the ways in which our project relied on art to engage young people in research, but, perhaps more importantly, to communicate complex symbolism, cultural values, Indigenous solidarity, and community healing through artistic expression. Using art as research was an endeavor to aspire to Kayanere'kowa [the Great Law of Peace] by manifesting sken:nen [peace], ka'hsatstenshera [power], and ka'nikonhri:yo [the Good Mind].